A silicon-carbon composite material and its preparation method and application
By injecting organic silane gas and organic carbon source gas into the autoclave and increasing the pressure in the kettle with nitrogen, co-deposition and uniform mixing of silicon and carbon are achieved, solving the problems of poor mixing uniformity between silicon and carbon and low material expansion in the prior art, and improving the specific capacity and electronic conductivity of silicon-carbon composite materials.
Patent Information
- Application Number
- CN202211704105.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-12-29
AI Technical Summary
When preparing silicon-carbon materials, there are defects such as poor mixing uniformity between silicon and carbon, long reaction time, easy growth of silicon grains, small improvement in performance, and low material expansion.
Porous carbon and organic catalyst are fully mixed, and organic silane gas, organic carbon source gas and nitrogen are introduced into the autoclave. After heating, the heat is insulated, and the silicon-carbon composite material is obtained. This method realizes co-deposition and uniform mixing of silicon and carbon by silane cracking, and uses nitrogen to increase the pressure in the kettle to reduce the expansion of silicon, and then forms amorphous carbon for coating by cracking the organic carbon source.
The uniform mixing of silicon and carbon at the atomic level is achieved, the specific capacity and electronic conductivity of the material are improved, the expansion and polarization of the material are reduced, and the rate performance and liquid absorption and liquid retention ability are improved.
Smart Images

Figure CN116014100B_ABST
Abstract
Description
Technical Field
[0001] The patent of this invention belongs to the field of lithium-ion battery materials, and specifically relates to a silicon-carbon composite material and its preparation method and application. Background Art
[0002] Silicon-carbon materials are widely used in lithium-ion batteries, 3C digital products and other fields due to their high energy density. At present, the main method for preparing silicon-carbon materials is sand milling, which grinds micron silicon to less than 100nm through a ball mill, and the silicon grains are about 20nm, and then coats amorphous carbon to obtain silicon-carbon materials. However, this method has problems such as self-agglomeration of nano-silicon and easy oxidation of nano-silicon, resulting in low initial efficiency.
[0003] The gas silane cracking method is to crack silicon at high temperature to generate silicon grains with a size of ≤5nm and deposit them in porous carbon to obtain a silicon-carbon composite material, which has the advantages of low expansion, high specific capacity, and high first efficiency. However, it has defects such as large safety risks in the preparation process, deviation in deposition uniformity, low reaction efficiency and small production capacity. Chinese patent document CN114551816A discloses a method for preparing a silicon-carbon composite material using organic silane, wherein a silicon oxide and carbon composite coating layer formed by an in-situ coating method of synchronous polymerization of silane and chemical acid resistance is deposited on the surface of nano-silicon particles to form a silicon oxide / carbon film coating the surface of the nano-silicon particles, the material after the reaction is centrifugally dried, and then the composite coating layer of the material is pyrolyzed into silicon dioxide / amorphous carbon under an inert protective gas; however, the raw material silicon oxygen of this scheme is 3-aminopropyltriethoxysilane, and due to the presence of oxygen, the electronic impedance of the material is relatively high, and the reaction is a liquid phase reaction, which has the defects of poor mixing uniformity of silicon and carbon, long reaction time, and easy growth of silicon grains, and the improvement in rate performance is not large, and there is no obvious improvement in reducing material expansion. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is the defects of poor mixing uniformity of silicon and carbon, long reaction time, easy growth of silicon grains, small performance improvement and low material expansion during the existing preparation of silicon-carbon materials, thereby providing a silicon-carbon composite material and its preparation method and application.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] The present invention provides a method for preparing a silicon-carbon composite material, comprising:
[0007] S1: The porous carbon and the organic catalyst are fully mixed and placed in a high-pressure reactor;
[0008] S2: introducing organosilane gas, organic carbon source gas and nitrogen;
[0009] S3: Keep warm after heating;
[0010] S4: cooling and washing to obtain the silicon-carbon composite material.
[0011] The mass ratio of porous carbon, organic catalyst, organic silane gas and organic carbon source gas is 30-60:1-5:100:10-50.
[0012] Preferably, the organosilane comprises at least one of trivinylsilane, tetravinylsilane, phenyltrivinylsilane, methyltrivinylsilane, triallylsilane and tetraallylsilane;
[0013] The organic carbon source includes at least one of polyethylene, polystyrene, polybutadiene, polyaniline, polypyrrole, and polythiophene;
[0014] The organic catalyst includes at least one of 1,1-bis(diphenylphosphino)ferrocenepalladium dichloride, 4,5-bis(diphenylphosphino)-9,9-dimethylxanthenepalladium dichloride, bis(diphenylphosphinophenyl ether)palladium dichloride, tris(dibenzylidene indeneacetone)dipalladium, cerium isopropoxide, cerium stearate, cerium trifluoromethanesulfonate, and cerium bis(trifluoromethanesulfonyl)imide.
[0015] Furthermore, in step S2, nitrogen is added to make the pressure in the high-pressure reactor 5-10 MPa.
[0016] In step S3, the temperature is increased to 200-500°C at a rate of 1-10°C / min;
[0017] The insulation time is 1-6h.
[0018] In step S4, the cooling is cooling to room temperature; and the washing is washing with dilute hydrochloric acid and then with deionized water.
[0019] Preferably, the porous carbon has a pore size of 10-50 nm and a specific surface area of ≥200 m 2 / g, particle size is 0.2μm-1.5μm.
[0020] The present invention also provides a silicon-carbon composite material, which is prepared by the above preparation method.
[0021] The above silicon-carbon composite material is applied to lithium-ion batteries.
[0022] The technical solution of the present invention has the following advantages:
[0023] (1) The present invention simultaneously adds silicon source gas and carbon source gas during the deposition process, so that silicon and carbon are co-deposited. The silicon source gas and the carbon source gas are simultaneously cracked to generate carbon free radicals and silicon free radicals, which can achieve uniform mixing of silicon and carbon at the atomic level. Compared with physical mixing, it has the characteristics of high uniformity and stable structure. At the same time, co-deposition can avoid adverse effects such as agglomeration.
[0024] (2) The present invention uses nitrogen to increase the pressure in the reactor during deposition. Under positive pressure conditions, silane is cracked to generate silicon grains that are deposited in the porous carbon, which reduces the expansion of silicon and generates amorphous carbon for coating by cracking the organic carbon source, thereby improving high-temperature performance. At the same time, the silicon-carbon dispersion obtained under positive pressure conditions is better than that under negative pressure conditions, and the reaction progress is faster.
[0025] (3) The present invention doped with organic catalysts can reduce the expansion of silicon grains by utilizing the holes formed by the catalytic pore-forming effect of the catalysts. At the same time, the organic catalysts can accelerate the reaction process of the materials and increase the reaction speed of the materials. Compared with inorganic catalysts, the nitrogen, carbon and other elements generated after the reaction of organic catalysts can increase the electronic conductivity of the materials and reduce the introduction of impurities.
[0026] (4) The silicon source of the present invention uses carbon-containing, oxygen-free silane gas, which can form more pores, reduce expansion and improve electronic conductivity.
[0027] (5) The carbon source of the present invention uses polymer gas, which has the advantages of low carbon source cracking temperature, etc., which can avoid the expansion caused by the growth of silicon grains at high temperature, so that the resulting material has the advantages of low expansion and high carbon coating integrity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is the SEM image of the silicon-carbon composite material obtained in Example 1. DETAILED DESCRIPTION
[0030] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0031] If no specific experimental steps or conditions are specified in the examples, the experiments can be carried out according to the conventional experimental steps or conditions described in the literature in the art.
[0032] Example 1
[0033] This embodiment provides a silicon-carbon composite material, and the specific preparation method is as follows:
[0034] Weigh 40 g of porous carbon (pore size 30 nm, specific surface area 300 m 2 / g, particle size: 1μm), 3g 1,1-bis(diphenylphosphino)ferrocenepalladium dichloride were transferred to a high-pressure reactor and mixed evenly, and then 100g trivinylsilane gas (flow rate 10ml / min) and 30g polyethylene gas (flow rate 10ml / min) were introduced at the same time, and high-purity nitrogen was introduced to make the pressure in the chamber 8Mpa, and then the temperature was increased to 300℃ at a heating rate of 5℃ / min for co-deposition and kept warm for 3h, and then cooled to room temperature, and then washed 10 times with 0.1mol / L dilute hydrochloric acid and deionized 10 times to obtain a silicon-carbon composite material.
[0035] Example 2
[0036] This embodiment provides a silicon-carbon composite material, and the specific preparation method is as follows:
[0037] Weigh 30 g of porous carbon (pore size 10 nm, specific surface area 400 m 2 / g, particle size: 0.2μm), 1g4,5-bis(diphenylphosphine)-9,9-dimethyloxanthene palladium dichloride were transferred to a high-pressure reactor and mixed evenly, and then 100g tetravinylsilane gas (flow rate 10ml / min) and 10g polystyrene gas (flow rate 10ml / min) were introduced at the same time, and high-purity nitrogen was introduced to make the pressure in the chamber 5Mpa, and then the temperature was increased to 200℃ at a heating rate of 1℃ / min for co-deposition and kept warm for 6h, and then cooled to room temperature, and then washed 10 times with 0.1mol / L dilute hydrochloric acid and deionized 10 times to obtain a silicon-carbon composite material.
[0038] Example 3
[0039] This embodiment provides a silicon-carbon composite material, and the specific preparation method is as follows:
[0040] 60g of porous carbon (pore size 50nm, specific surface area: 200m2 / g, particle size: 1.5μm) and 5g of bis(diphenylphosphinophenyl ether)palladium dichloride were transferred to a high-pressure reactor, and then 100g of methyltrivinylsilane gas and 50g of polybutadiene gas were introduced at the same time, and high-purity nitrogen was introduced to make the pressure in the chamber 10Mpa. Then, the temperature was increased to 500℃ at a heating rate of 10℃ / min for co-deposition and kept warm for 1h, and then cooled to room temperature, and then washed 10 times with 0.1mol / L dilute hydrochloric acid and deionized 10 times to obtain a silicon-carbon composite material.
[0041] Comparative Example 1
[0042] This comparative example provides a silicon-carbon composite material, which is prepared by a sand milling method. The specific preparation method is as follows: micron silicon is ground to 100 nm by a sand mill, and then 50 g is taken and added to 100 g of asphalt and 50 g of natural graphite to mix evenly, and then ground under an inert atmosphere, and then transferred to a tubular furnace, and an inert gas is introduced to remove the air in the tube, and then methane gas (flow rate 50 ml / min) is passed, and heated to 800°C for carbonization for 3 hours, and then the temperature is reduced to room temperature in an argon atmosphere, and the silicon-carbon composite material is crushed.
[0043] Comparative Example 2
[0044] This comparative example provides a silicon-carbon composite material, and the specific preparation method is as follows:
[0045] Weigh 40 g of porous carbon (pore size 30 nm, specific surface area 300 m 2 / g, particle size: 1μm), 3g 1,1-bis(diphenylphosphino)ferrocenepalladium dichloride were transferred to a high-pressure reactor and mixed evenly, and then 100g trivinylsilane gas (flow rate 10ml / min) was introduced, and high-purity nitrogen was introduced to make the pressure in the chamber 8Mpa, and then the temperature was increased to 300℃ at a heating rate of 5℃ / min for deposition and kept warm for 3h, and then 30g polyethylene gas (flow rate 10ml / min) was introduced, and the heat preservation was continued for 3h, and then the temperature was cooled to room temperature, and then washed 10 times with 0.1mol / L dilute hydrochloric acid and 10 times with deionization to obtain a silicon-carbon composite material.
[0046] Comparative Example 3
[0047] This comparative example provides a silicon-carbon composite material, which is different from Example 1 in that nitrogen is not introduced.
[0048] Comparative Example 4
[0049] This comparative example provides a silicon-carbon composite material, which is different from Example 1 in that polyethylene gas is replaced by ethylene gas.
[0050] Comparative Example 5
[0051] This comparative example provides a silicon-carbon composite material, which is different from Example 1 in that the catalyst is changed to cobalt chloride.
[0052] Test Example 1
[0053] The silicon-carbon composite material in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the material presents a granular structure, and the particle size distribution of the material is uniform and reasonable, and the particle size is between 10-20μm.
[0054] Test Example 2
[0055] The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-5 were used as negative electrode materials for lithium-ion batteries and assembled into button batteries, which were respectively denoted as A1, A2, A3, B1, B2, B3, B4, and B5.
[0056] The specific preparation method is as follows: add a binder, a conductive agent and a solvent to the negative electrode material of a lithium-ion battery, stir to make a slurry, apply it on a copper foil, dry and roll to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is SP, the solvent is NMP, and the amount ratio of the negative electrode material, SP, PVDF, and NMP is 95g:1g:4g:220mL; LiPF in the electrolyte 6 The electrolyte is a mixture of EC and DEC with a volume ratio of 1:1 as the solvent; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film. The button cell is assembled in an argon-filled glove box. The electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C.
[0057] At the same time, the specific surface area, tap density and powder conductivity are tested according to the national standard GBT-38823-2020 "Silicon Carbon". At the same time, the silicon grains are tested by XRD.
[0058] The test results are shown in Table 1.
[0059] Table 1 Button battery performance test results
[0060]
[0061] It can be seen from the data in Table 1 that the specific capacity and the first efficiency of the silicon-carbon composite material prepared by each embodiment of the present invention are significantly better than those of the comparative example. The reason is that: the embodiment of the present invention can make nano-silicon uniformly coated in the porous carbon pores by the silane cracking method, and deposit amorphous carbon on this as a matrix, reduce impedance and reduce the polarization of the material, and improve the specific capacity of the material; at the same time, the material prepared by the silane cracking method has the characteristics of high density and its doping with metal, thereby improving the tap density of the material and improving the conductivity of the powder. In Comparative Example 2, the simultaneous introduction of trivinylsilane and polyethylene is changed to sequential introduction, so that the mixing is not uniform, and there may be a problem of agglomeration; in Comparative Example 3, nitrogen is not introduced, and the environment will become a negative pressure state with the reaction, slowing down the reaction process, and the silicon obtained will expand greatly; in Comparative Example 4, ethylene is used instead of polyethylene, the carbon-carbon chemical bond is poor, the impedance is large, the structural stability is biased, and the tap density is low; in Comparative Example 5, an inorganic catalyst is used, and impurities will be added after the reaction, affecting the electronic conductivity. Finally, the silicon-carbon materials obtained in each comparative example are significantly lower than those in each embodiment when applied to batteries.
[0062] Test Example 3
[0063] Soft pack battery test: The silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-5 were doped with 90% artificial graphite as negative electrode materials to prepare negative electrode sheets, and NCM532 was used as positive electrode material; LiPF 6 As electrolyte, a mixture of EC and DEC with a volume ratio of 1:1 was used as solvent; Celgard 2400 membrane was used as separator to prepare 5Ah soft-pack batteries, which were marked as C1, C2, C3, D1, D2, D3, D4, and D5. The liquid absorption and retention capacity of the negative electrode, the electrode rebound, and the cycle performance were tested respectively.
[0064] a. Liquid absorption capacity test:
[0065] Use a 1mL burette and absorb VmL of electrolyte, add a drop on the surface of the electrode, and count until the electrolyte is completely absorbed, record the time t, and calculate the electrode's liquid absorption rate V / t. The test results are shown in Table 2.
[0066] b. Liquid retention rate test:
[0067] According to the electrode parameters, calculate the theoretical liquid absorption of the electrode m 1 , and weigh the weight of the pole piece m 2 Then, place the electrode in the electrolyte and soak it for 24 hours. The weight of the electrode is m 3 , calculate the amount of liquid absorbed by the electrode m 3 -m 2 , and calculated according to the following formula: Liquid retention rate = (m 3 -m 2)*100% / m1. The test results are shown in Table 2.
[0068] Table 2 Test results of liquid absorption capacity and liquid retention rate
[0069]
[0070]
[0071] As can be seen from Table 2, the liquid absorption and liquid retention capacity of the silicon composite materials obtained in Examples 1-3 is significantly higher than that of Comparative Examples 1-5. The experimental results show that the silicon-carbon composite material of the present invention has a higher liquid absorption and liquid retention capacity. The reason is that the specific surface area of the composite material of the embodiment is larger, which improves the liquid absorption and liquid retention capacity of the material.
[0072] c. Electrode full charge rebound rate test:
[0073] First, the thickness of the electrode sheet was tested with a thickness gauge to be D1, and then the prepared battery was fully charged to 100% SOC, and then the battery was dissected to test the thickness of the negative electrode sheet to be D2, and the rebound rate was calculated according to the following formula: (D2-D1)*100% / D1. The test results are shown in Table 3.
[0074] d. Electrode resistivity test
[0075] The resistivity of the electrode was tested using a resistivity tester, and the test results are shown in Table 3.
[0076] Table 3 Test results of electrode full charge rebound rate and electrode resistivity
[0077]
[0078]
[0079] From the data in Table 3, it can be seen that the rebound rate and resistivity of the negative electrode sheet prepared by the silicon-carbon composite material obtained in Examples 1-3 are significantly lower than those in the comparative example, that is, the negative electrode sheet prepared by the silicon-carbon composite material of the present invention has a lower rebound rate and resistivity. The reason is that: the method in the embodiment of the present application can uniformly deposit nano-silicon in the porous carbon and coat amorphous carbon on its surface to reduce impedance; at the same time, the silicon grains of the embodiment material are smaller, which reduces expansion.
[0080] e. Rate performance test
[0081] Charge rate: 1C / 2C / 3C / 5C, discharge rate 1C; voltage range: 2.5-4.2V. Test results are shown in Table 4.
[0082] Table 4 Rate performance test
[0083]
[0084] It can be seen from Table 4 that the silicon-carbon composite material of the present invention has an excellent constant current ratio, that is, an excellent fast charging performance. The reason is that the material prepared in the embodiment has a lower powder resistivity and amorphous carbon with high densification, thereby improving the fast charging performance of the material, that is, a high constant current ratio.
[0085] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a silicon-carbon composite material, characterized in that: include: S1: The porous carbon and the organic catalyst are fully mixed and placed in a high-pressure reactor; S2: introducing organosilane gas, organic carbon source gas and nitrogen; wherein the organosilane gas and organic carbon source gas are introduced simultaneously; S3: Keep warm after heating; S4: cooling and washing to obtain the silicon-carbon composite material; The organosilane comprises at least one of trivinylsilane, tetravinylsilane, phenyltrivinylsilane, methyltrivinylsilane, triallylsilane and tetraallylsilane; The organic carbon source includes at least one of polyethylene, polystyrene, and polybutadiene; The organic catalyst includes at least one of 1,1-bis(diphenylphosphino)ferrocenepalladium dichloride, 4,5-bis(diphenylphosphino)-9,9-dimethylxanthenepalladium dichloride, bis(diphenylphosphinophenyl ether)palladium dichloride, tris(dibenzylidene indeneacetone)dipalladium, cerium isopropoxide, cerium stearate, cerium trifluoromethanesulfonate, and cerium bis(trifluoromethanesulfonyl)imide.
2. The preparation method according to claim 1, characterized in that: The mass ratio of porous carbon, organic catalyst, organic silane gas and organic carbon source gas is 30-60:1-5:100:10-50.
3. The preparation method according to claim 2, characterized in that: In step S2, nitrogen is added to make the pressure in the high-pressure reactor 5-10 MPa.
4. The preparation method according to claim 3, characterized in that: In step S3, the temperature is increased to 200-500°C at a rate of 1-10°C / min; The insulation time is 1-6h.
5. The preparation method according to claim 4, characterized in that: In step S4, the cooling is performed naturally to room temperature; and the washing is performed by washing with dilute hydrochloric acid and then with deionized water.
6. The preparation method according to claim 5, characterized in that: The porous carbon has a pore size of 10-50 nm and a specific surface area of ≥200 m 2 / g, particle size is 0.2μm-1.5μm.
7. A silicon-carbon composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the silicon-carbon composite material according to claim 7, characterized in that: Applied to lithium-ion batteries.
Citation Information
Patent Citations
Method for preparing silicon-carbon composite material by using organosilane
CN114551816A
Porous carbon doping induced silicon deposition silicon-carbon negative electrode material and preparation method thereof
CN114122352A